Association between study year and depressive and anxious symptoms during the first months of confinement due to COVID-19 pandemic in a sample of medical students from a private university in Lima, Peru. - Krüger-Malpartida, Hever (2022)
Objective: To determine the relationship between year levels of medical studies and depressive and anxious symptoms during the first months of the COVID-19 pandemic in a sample of medical students in Lima, controlling specifically the variables sex and presence of underlying medical conditions. Material and Methods: An online survey collected information from 250 medical students, covering general data, previous medical history and symptoms of depression (PHQ-9) and anxiety (GAD-7). Data were managed using multivariate analysis of covariance. Results: Differences were found between years of study and the combined values of PHQ-9 and GAD-7 (Wilks’ Λ = 0.86; p = 1.68 x 10-4; η2p = 0.08). Underlying medical conditions also showed significant differences for the combined values of PHQ-9 and GAD-7 (Wilks’ Λ = 0.94, p = 4.43 x 10-4, η2p = 0.06). The univariate test for year of study showed differences for PHQ-9 (F6.241 = 4.12, p = 0.001, η2p = 0.09) and GAD-7 (F6.241 = 2.81, p = 0.01, η2p = 0.07). The post hoc analysis showed statistically significant differences in the first years of study. Conclusions: These results suggest that medical students of the first years show higher levels of depression and anxiety symptoms than participants from more advanced years of the medical career. Likewise, the occurrence of previous medical conditions also explained high levels of depression and anxiety.